2003
DOI: 10.1038/sj.gt.3301957
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cancer escape variants that evade immunogene therapy through loss of sensitivity to IFNγ-induced apoptosis

Abstract: Combined injections into experimental tumor nodules of adenovirus encoding IL-12 and certain chemokines are capable to induce immune-mediated complete regressions. In this study, we found that the combination of two adenoviruses, one encoding IL-12 and other MIP3a (Ad-CMVIL-12+AdCMVMIP3a) was very successful in treating CT-26-derived colon carcinomas. However, in experimental tumors generated from the pancreatic carcinoma cell line Panc02 such combined treatment induces 50% of macroscopic complete regressions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 54 publications
(84 reference statements)
2
12
0
Order By: Relevance
“…The complex genetic changes leading to acquired resistance to PD-1 blockade, wherein one JAK1/2 allele was mutated and amplified and the other was lost, suggest a strong selective pressure induced by the therapeutic immune response. Similar events leading to lack of sensitivity to interferon gamma have been reported in the cancer immune-editing process and acquired resistance to immunotherapy in mouse models (1517) and in patients treated with the anti-CTLA-4 antibody ipilimumab who did not respond to therapy (18). Therefore, lack of interferon gamma responsiveness allows cancer cells to escape from antitumor T cells, and in the context of anti-PD-1/L1 therapy, results in the loss of PD-L1 expression, the target of PD-1 blockade therapy, which would abrogate the antitumor efficacy of this approach.…”
Section: Introductionsupporting
confidence: 57%
“…The complex genetic changes leading to acquired resistance to PD-1 blockade, wherein one JAK1/2 allele was mutated and amplified and the other was lost, suggest a strong selective pressure induced by the therapeutic immune response. Similar events leading to lack of sensitivity to interferon gamma have been reported in the cancer immune-editing process and acquired resistance to immunotherapy in mouse models (1517) and in patients treated with the anti-CTLA-4 antibody ipilimumab who did not respond to therapy (18). Therefore, lack of interferon gamma responsiveness allows cancer cells to escape from antitumor T cells, and in the context of anti-PD-1/L1 therapy, results in the loss of PD-L1 expression, the target of PD-1 blockade therapy, which would abrogate the antitumor efficacy of this approach.…”
Section: Introductionsupporting
confidence: 57%
“…Because IFN-␥ has multiple biological activities, and its receptor (IFN-␥R) is expressed in almost all cell types (39,40), this cytokine might have direct effects on tumor cells such as: 1) inhibiting cell proliferation or sensitizing cells to apoptosis (41,42); 2) up-regulating MHC class I expression and thereby increasing tumor cell lysis (43); 3) up-regulating MHC class II expression on tumor cells (44,45), 4) stimulating NK activity (46), or 5) inducing the expression of angiogenesis inhibitors, like IFN-␥-inducible protein-10, by tumor and stromal cells (47). We have not found any inhibitory effect of IFN-␥ on proliferation of CT26 tumor cells in vitro even at doses of 7500 U/ml (around 3 ϫ 10 6 pg/ml) (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The authors detected an infiltrate of CD11c cells in the tumour and also in draining lymph nodes, which became enlarged. In a subsequent study [132], also with an adenovirus encoding MIP-3α, it was found that it was synergistic with gene transduction of the tumour with IL-12 by means of recombinant adenovirus, achieving complete regressions in CT26 and the experimental pancreatic carcinoma PANC02. In both studies, the antitumour effect was dependent on T cells and correlated with CTL responses.…”
Section: Attracting Endogenous Dendritic Cells To the Tumour Tissue Amentioning
confidence: 97%